Modified porous alumina as well as preparation method and application thereof
By loading the modification additives in porous alumina and controlling its structural characteristics, the problem of the lithium-ion battery separator being easily contracted or melted at high temperatures is solved, and high liquid retention, HF capture capability and battery safety are improved.
Patent Information
- Application Number
- CN202411788204.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-11
AI Technical Summary
The separator in lithium-ion batteries is prone to shrink or melt at high temperatures, resulting in internal short circuits, fires and even explosions. In the prior art, liquid absorption and liquid retention are not ideal when improving thermal stability.
Modified porous alumina is used, which improves its wetting properties and HF capture capabilities by loading modification auxiliaries in porous alumina such as pyridine, imidazole, indole, quinoline and morpholine, and controls its particle size, pore volume and pore size through specific preparation methods.
It realizes the high liquid retention volume, high ionic conductivity and high wettability of the separator, while effectively capturing the HF free in the electrolyte, improving the reliability and safety of lithium-ion batteries.
Smart Images

Figure CN119591133A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of diaphragm materials, and in particular to a modified porous alumina and a preparation method and application thereof. Background Art
[0002] The electrolyte and separator are the two most important components in lithium batteries, affecting the performance of lithium-ion batteries. The liquid electrolyte in the battery is composed of lithium salts and organic solvents and is extremely sensitive to moisture. Moisture inside the battery triggers the hydrolysis of lithium salts to produce lithium fluoride (LiF) and highly corrosive hydrofluoric acid (HF). HF in turn attacks the cathode electrolyte interface (CEI) and solid electrolyte interface (SEI), causing harmful transition metals to dissolve from the cathode and causing severe parasitic reactions in the electrolyte, ultimately impairing the electrochemical performance of the battery.
[0003] The materials of the battery diaphragm are mainly polypropylene (PP) and polyethylene (PE), and their melting points are 165°C and 135°C respectively. Therefore, at high temperatures, the diaphragm is easy to shrink or melt, causing internal short circuits, leading to fires and even explosions. In view of the above situation, the prior art provides a variety of methods to improve the thermal stability of the diaphragm, such as incorporating inorganic materials into organic films to obtain composite diaphragms, or using organic or inorganic films with high thermal stability, but the liquid absorption and liquid retention are not ideal.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] The purpose of the present invention includes providing a modified porous alumina and a preparation method and application thereof to solve or improve the above-mentioned technical problems.
[0006] The present invention can be implemented like this:
[0007] In a first aspect, the present invention provides a modified porous alumina, which comprises porous alumina and a modification aid supported in the pore structure of the porous alumina;
[0008] The modification aid includes at least one of pyridine, imidazole, indole, quinoline and morpholine; the mass ratio of the porous alumina to the modification aid is 100:1 to 100:40;
[0009] The particle size of porous alumina is 0.1 μm to 2 μm;
[0010] The pore volume of porous alumina is 0.01 cm 3 / g~0.1cm 3 / g;
[0011] The pore size of porous alumina is 3nm to 50nm.
[0012] In a second aspect, the present invention provides a method for preparing a modified porous alumina powder according to the aforementioned embodiment, comprising the following steps:
[0013] The aluminum salt, the doping aid and water are mixed and subjected to a first hydrothermal reaction to obtain an aluminum oxide reactant;
[0014] The alumina reactant is dried and then calcined to obtain porous alumina;
[0015] The porous alumina is mixed with a modification aid and water, subjected to a second hydrothermal reaction, and dried to obtain modified porous alumina.
[0016] In an alternative embodiment, the aluminum salt includes at least one of aluminum nitrate nonahydrate, aluminum nitrate, aluminum alkoxide, and aluminum hydroxide.
[0017] In an alternative embodiment, the aluminum salt is selected from aluminum hydroxide.
[0018] In an optional embodiment, the amount of the doping aid added is 0.01 wt% to 1 wt% of the aluminum salt;
[0019] And / or, the doping aid includes at least one of triquaternary ammonium and trimethylammonium.
[0020] In an optional embodiment, the temperature of the first hydrothermal reaction is 120° C. to 240° C., and / or the time of the first hydrothermal reaction is 4 h to 48 h.
[0021] In an optional embodiment, the chemical formula of the aluminum oxide reactant is Al2O3·nH2O, wherein 1≤n≤2;
[0022] and / or, the particle size of the alumina reactant is 0.1 μm to 2 μm;
[0023] And / or, the crystal water content of the alumina reactant is 17 wt% to 30 wt%.
[0024] In an optional embodiment, the calcination temperature is 500°C to 1200°C;
[0025] And / or, the calcination time is 0.5h to 10h;
[0026] And / or, the heating rate during the calcination process is 1°C / min to 10°C / min.
[0027] In an optional embodiment, the temperature of the second hydrothermal reaction is 90° C. to 190° C., and / or the time of the second hydrothermal reaction is 4 h to 48 h.
[0028] In a third aspect, the present invention provides a battery separator, which includes a separator substrate and a coating located on at least one side of the separator substrate, wherein the coating contains the modified porous alumina of the aforementioned embodiment.
[0029] In an alternative embodiment, the contact angle of the battery separator with water is <35°.
[0030] In a fourth aspect, the present invention provides a battery, comprising the battery separator of the aforementioned embodiment.
[0031] The beneficial effects of the present invention include:
[0032] The porous alumina in the modified porous alumina provided by the present invention has a smaller particle size, which can realize the setting of a thinner coating of the diaphragm; the porous alumina in the modified porous alumina has a specific pore volume and pore size, which is beneficial to improving the liquid retention and ion conductivity of the diaphragm; in addition, the porous alumina in the modified porous alumina is also loaded with a modification aid, which can not only improve the wetting performance, but also effectively capture HF free in the electrolyte, thereby improving the reliability and safety of the lithium ion battery.
[0033] The preparation method of the modified porous alumina is simple and easy to operate.
[0034] The modified porous alumina provided by the present invention is used for coating a battery diaphragm, and while obtaining a diaphragm with high liquid retention and high ion conductivity, due to the loading of the modification auxiliary agent, the diaphragm has high wettability and HF adsorption effect, the contact angle between the diaphragm and water is small (for example, <35°), the wettability is greatly improved, and a large portion (for example, more than 78.5%) of HF in the electrolyte can be removed. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0036] Figure 1 This is a SEM image of the porous alumina prepared in Example 1;
[0037] Figure 2 This is the SEM image of conventional alumina in Comparative Example 1. DETAILED DESCRIPTION
[0038] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0039] The modified porous alumina provided by the present invention and its preparation method and application are described in detail below.
[0040] The invention provides a modified porous alumina, which comprises porous alumina and a modification aid loaded in the pore structure of the porous alumina.
[0041] Wherein, the modification aid includes at least one of pyridine, imidazole, indole, quinoline and morpholine.
[0042] The addition of the above-mentioned modification aid can effectively improve the surface structure of the porous alumina, making it easier to combine with water, thereby improving the wettability of the modified porous alumina; and, the NH sites carried by the above-mentioned modification aid can effectively capture HF, so that the modified porous alumina has the function of removing HF; in addition, the use of the above-mentioned modification aid is also conducive to maintaining the porous characteristics of the material.
[0043] In the present invention, the mass ratio of porous alumina to the modification aid can be 100:1 to 100:40, such as 100:1, 100:2, 100:5, 100:8, 100:10, 100:15, 100:20, 100:25, 100:30, 100:35 or 100:40, etc., and can also be other values within the range of 100:1 to 100:40. In some typical embodiments, the mass ratio of porous alumina to the modification aid can be 100:1 to 100:38.
[0044] If the mass ratio of porous alumina to the modifying agent is less than 100:1 (such as 100:0.5), the modified porous alumina will not be able to adsorb HF and improve wettability; if the mass ratio of porous alumina to the modifying agent is greater than 100:40 (such as 100:50), not only will the adsorption effect of the modified porous alumina not be further improved, but the pore volume and pore size of the modified porous alumina will also decrease, affecting the lithium ion transmission effect.
[0045] In some optional embodiments, the particle size of the porous alumina is 0.1 μm to 2 μm, such as 0.1 μm, 0.2 μm, 0.5 μm, 0.8 μm, 1 μm, 1.2 μm, 1.5 μm, 1.8 μm or 2 μm, etc., or other values within the range of 0.1 μm to 2 μm.
[0046] The above particle size is conducive to achieving the performance requirements of mainstream lithium battery separator coating. If the particle size of porous alumina is less than 0.1μm, it is not conducive to the air permeability of the coated separator, which will cause the electrolyte to be unable to be effectively transmitted on both sides of the separator, thereby affecting HF adsorption; if the particle size of porous alumina is greater than 2μm, it cannot meet the current mainstream separator companies' requirements for coating thickness (<2.5μm).
[0047] In some optional embodiments, the pore volume of the porous alumina is 0.01 cm 3 / g~0.1cm 3 / g, such as 0.01cm 3 / g, 0.02cm 3 / g, 0.04cm 3 / g, 0.06cm 3 / g, 0.08cm 3 / g or 0.1cm 3 / g, etc., can also be 0.01cm 3 / g~0.1cm 3 / Other values within the range of g.
[0048] The above pore volume is conducive to the doping of the modification additive. If the pore volume of porous alumina is less than 0.01 cm 3 / g, which is not conducive to the loading of modified additives; if the pore volume of porous alumina is greater than 0.1cm 3 / g, which will lead to the loss of modification additives.
[0049] In some optional embodiments, the pore size of the porous alumina is 3nm to 50nm, such as 3nm, 5nm, 8nm, 10nm, 15nm, 20nm, 25nm, 30nm, 35nm, 40nm, 45nm or 50nm, etc., or other values within the range of 3nm to 50nm.
[0050] The above pore size is conducive to the doping of the modification agent. If the pore size of the porous alumina is less than 3nm, it is not conducive to the loading of the modification agent; if the pore size of the porous alumina is greater than 50nm, it will cause the modification agent to be lost.
[0051] The porous alumina in the modified porous alumina has the above-mentioned pore volume and pore diameter, and can have a higher liquid retention capacity and higher ion conductivity.
[0052] As mentioned above, the porous alumina in the modified porous alumina provided by the present invention has a smaller particle size, which can realize the setting of a thinner coating of the diaphragm; the porous alumina in the modified porous alumina has a specific pore volume and pore size, which is beneficial to improving the liquid retention and ion conductivity of the diaphragm; in addition, the porous alumina in the modified porous alumina is also loaded with a modification aid, which can not only improve the wetting performance, but also effectively capture HF free in the electrolyte, thereby improving the reliability and safety of the lithium-ion battery.
[0053] Accordingly, the present invention also provides a method for preparing the modified porous alumina, comprising the following steps:
[0054] S1: mixing aluminum salt, doping aid and water and performing a first hydrothermal reaction to obtain an aluminum oxide reactant.
[0055] In some optional embodiments, the aluminum salt may illustratively but not limitatively include at least one of aluminum nitrate nonahydrate, aluminum nitrate, aluminum alcoholate, and aluminum hydroxide. The above aluminum salt can be dissolved in pure water at room temperature and pressure, is easy to carry out hydrothermal reaction, and will not corrode the pipeline of the hydrothermal reaction. In some more typical embodiments, the aluminum salt is selected from aluminum hydroxide.
[0056] In some optional embodiments, the amount of doping aid added is 0.01wt% to 1wt% of the alumina reactant, such as 0.01wt%, 0.05wt%, 0.1wt%, 0.2wt%, 0.5wt%, 0.8wt% or 1wt%, etc., and can also be other values within the range of 0.01wt% to 1wt%.
[0057] If the amount of the doping aid added exceeds 1 wt %, the morphology of the alumina reactant will be poor, affecting the pore volume and pore size of the porous alumina.
[0058] In some optional embodiments, the doping aid includes at least one of triquaternary ammonium and trimethylammonium.
[0059] In some optional embodiments, the material-water ratio used in the first hydrothermal reaction is 1:10 to 1:2.5, such as 1:10, 1:9, 1:8, 1:7, 1:6, 1:5, 1:4, 1:3 or 1:2.5, etc., or other values within the range of 1:10 to 1:2.5.
[0060] In some optional embodiments, the temperature of the first hydrothermal reaction is 120°C to 240°C, such as 120°C, 140°C, 160°C, 180°C, 200°C, 220°C or 240°C, etc., or other values within the range of 120°C to 240°C.
[0061] The time of the first hydrothermal reaction can be 4 h to 48 h, such as 4 h, 8 h, 12 h, 16 h, 20 h, 24 h, 28 h, 32 h, 36 h, 40 h, 44 h or 48 h, or other values within the range of 4 h to 48 h.
[0062] In some optional embodiments, the general chemical formula of the aluminum oxide reactant is Al2O3·nH2O, wherein 1≤n≤2.
[0063] In some optional embodiments, the particle size of the aluminum oxide reactant may be 0.1 μm to 2 μm, such as 0.1 μm, 0.2 μm, 0.5 μm, 1 μm, 1.5 μm or 2 μm, or other values within the range of 0.1 μm to 2 μm.
[0064] In some optional embodiments, the crystal water content of the alumina reactant can be 17wt% to 30wt%, such as 17wt%, 20wt%, 22wt%, 25wt%, 28wt% or 30wt%, etc., or other values within the range of 17wt% to 30wt%.
[0065] As mentioned above, in this step, a uniform precursor solution is generated by dissolving aluminum salt in water and adding a doping aid, which can ensure the formation of a pore structure during the subsequent calcination process. The addition of a doping aid helps control the pore size and porosity of the final porous alumina so that it meets the required structural requirements and ensures the porous characteristics of the material.
[0066] S2: Drying the alumina reactant and then calcining it to obtain porous alumina.
[0067] In some optional embodiments, the alumina reactant may be dried by spray drying.
[0068] In some optional embodiments, the calcination temperature can be 500°C to 1200°C, such as 500°C, 600°C, 700°C, 800°C, 900°C, 1000°C, 1100°C or 1200°C, or other values within the range of 500°C to 1200°C.
[0069] The calcination time can be 0.5 h to 10 h, such as 0.5 h, 1 h, 2 h, 4 h, 6 h, 8 h or 10 h, etc., or other values within the range of 0.5 h to 10 h.
[0070] The heating rate during the calcination process can be 1°C / min to 10°C / min, such as 1°C / min, 2°C / min, 4°C / min, 6°C / min, 8°C / min or 10°C / min, or other values within the range of 1°C / min to 10°C / min.
[0071] The above calcination conditions will affect the pore volume and pore diameter of the porous alumina. Under the combined influence of the specific heating rate, calcination temperature and calcination time provided by the present invention, an alumina powder with a porous structure and controllable pore diameter and pore volume is obtained.
[0072] In this step, porous alumina having a porous structure with different pore volumes and pore sizes can be obtained without the assistance of additional sintering aids and pore-forming agents.
[0073] It should be emphasized that, in the present invention, porous alumina with a specific pore structure is obtained by combining S1 and S2, and the porous alumina has the characteristics of high liquid retention capacity and high ionic conductivity.
[0074] S3: Mix the porous alumina with the modification aid and water, perform a second hydrothermal reaction, and dry to obtain modified porous alumina.
[0075] In some optional embodiments, the material-water ratio used in the second hydrothermal reaction is 1:10 to 1:2.5, such as 1:10, 1:9, 1:8, 1:7, 1:6, 1:5, 1:4, 1:3 or 1:2.5, etc., or other values within the range of 1:10 to 1:2.5.
[0076] In some optional embodiments, the temperature of the second hydrothermal reaction can be 90°C to 190°C, such as 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C or 190°C, etc., or other values within the range of 90°C to 190°C.
[0077] The time of the second hydrothermal reaction can be 4 h to 48 h, such as 4 h, 8 h, 12 h, 16 h, 20 h, 24 h, 28 h, 32 h, 36 h, 40 h, 44 h or 48 h, or other values within the range of 4 h to 48 h.
[0078] As mentioned above, the preparation method provided by the present invention synthesizes an alumina reactant through the first hydrothermal reaction, and a porous alumina with a porous structure can be obtained without adding additional sintering aids and pore-forming agents during the subsequent calcination process; the porous alumina undergoes a second hydrothermal reaction to load the modified organic matter into the pore structure of the porous alumina, thereby obtaining a modified porous alumina with high wettability and good acid removal effect. When the modified porous alumina is used for coating a lithium-ion battery diaphragm, a thin coating diaphragm with high wettability can be obtained, and the diaphragm also has the function of adsorbing and removing HF.
[0079] It should be noted that the present invention does not exclude the use of other preparation methods, such as solid phase method, sol-gel method or seed precipitation method, to prepare the modified porous alumina having the characteristics of the present invention.
[0080] In addition, the present invention also provides a battery separator, which includes a separator substrate and a coating located on at least one side of the separator substrate, wherein the coating contains the modified porous alumina of the aforementioned embodiment.
[0081] By using the modified porous alumina provided by the present invention for coating a battery diaphragm, a diaphragm with high liquid retention and high ion conductivity is obtained. Due to the loading of the modification auxiliary agent, the diaphragm has high wettability and HF adsorption effect, the contact angle between the diaphragm and water is small (for example, <35°, preferably <27.5°), the wettability is greatly improved, and more than 78.5% of HF in the electrolyte can be removed.
[0082] It should be noted that the preparation of the coating can refer to the relevant prior art, and no further elaboration or limitation is given here. Optionally, the modified porous alumina prepared by the present invention can also be used in combination with other substances that can be used for diaphragms. The present invention is applicable to any solution that can be known to those skilled in the art within a reasonable range.
[0083] Furthermore, the present invention also provides a battery, which includes the above-mentioned battery separator and can have higher safety performance in use.
[0084] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0085] Example 1
[0086] This embodiment provides a modified porous alumina, the preparation method of which includes:
[0087] S1: 1 t of aluminum hydroxide, 0.1 kg of triquaternary ammonium and 2.4 t of pure water were added into a hydrothermal reactor, and a first hydrothermal reaction was carried out at 200° C. for 6 h to prepare an aluminum oxide reaction body.
[0088] The general chemical formula of the aluminum oxide reactant is Al2O3·nH2O, wherein the value of n is 1.1. The particle size of the aluminum oxide reactant is 0.7 μm, and the crystal water content of the aluminum oxide reactant is 17 wt%.
[0089] The added amount of the doping aid is 0.01 wt % of the aluminum salt.
[0090] S2: The alumina reactant was dried into powder by spray drying, and then placed in a crucible for calcination. Specifically, the heating rate was controlled at 5°C / min, the calcination temperature was controlled at 700°C, and the calcination time was 2h, and the particle size was 0.7μm and the pore volume was 0.09cm 3 / g, porous alumina with a pore size of 4nm (such as Figure 1 shown).
[0091] S3: Add 1 t of porous alumina, 10 kg of piperidine and 2.4 t of pure water into a hydrothermal reactor, carry out a second hydrothermal reaction at 120°C for 6 hours, spray-dry the reaction product to obtain modified porous alumina with a modification agent loading of 1 wt%.
[0092] Example 2
[0093] The difference between this embodiment and embodiment 1 is that the modification aid used in S3 is 180 kg of imidazole, and the modified porous alumina with a modification aid loading of 18 wt % is obtained.
[0094] Example 3
[0095] The difference between this embodiment and embodiment 1 is that the modification aid used in S3 is 200 kg of indole, and the second hydrothermal reaction is carried out at 130° C. for 6 hours to obtain a modified porous alumina with a modification aid loading of 20 wt %.
[0096] Example 4
[0097] The difference between this embodiment and embodiment 1 is that the modification aid used in S3 is 250 kg of quinoline, and the second hydrothermal reaction is carried out at 140° C. for 6 hours to obtain a modified porous alumina with a modification aid loading of 25 wt %.
[0098] Example 5
[0099] The difference between this embodiment and embodiment 1 is that the modification aid used in S3 is 300 kg of morpholine, and the second hydrothermal reaction is carried out at 150° C. for 6 hours to obtain a modified porous alumina with a modification aid loading of 30 wt %.
[0100] Example 6
[0101] The difference between this embodiment and embodiment 1 is that the modification aid used in S3 is 380 kg of piperidine, and the second hydrothermal reaction is carried out at 150° C. for 6 hours to obtain a modified porous alumina with a modification aid loading of 38 wt %.
[0102] Example 7
[0103] The difference between this embodiment and embodiment 1 is that the modification aid used in S3 is 50 kg of piperidine, and the second hydrothermal reaction is carried out at 150° C. for 6 hours to obtain a modified porous alumina with a modification aid loading of 5 wt %.
[0104] Example 8
[0105] The difference between this embodiment and embodiment 1 is that the modification aid used in S3 is 100 kg of piperidine, and the second hydrothermal reaction is carried out at 150° C. for 6 hours to obtain a modified porous alumina with a modification aid loading of 10 wt %.
[0106] Example 9
[0107] The difference between this embodiment and embodiment 1 is that the modification aid used in S3 is 270 kg of piperidine, and the second hydrothermal reaction is carried out at 150° C. for 6 hours to obtain a modified porous alumina with a modification aid loading of 27 wt %.
[0108] Example 10
[0109] The difference between this embodiment and embodiment 1 is that the modification aid used in S3 is 360 kg of piperidine, and the second hydrothermal reaction is carried out at 150° C. for 6 hours to obtain a modified porous alumina with a modification aid loading of 36 wt %.
[0110] Embodiment 11
[0111] The difference between this embodiment and embodiment 1 is that:
[0112] In S1, triquaternary ammonium is replaced by trimethylammonium, and the amount of trimethylammonium added is 0.5wt% of the aluminum salt. The first hydrothermal reaction is carried out at 120°C for 48h. The chemical formula of the aluminum oxide reaction body obtained in this step is Al2O3·nH2O, wherein the value of n is 1.1. The particle size of the aluminum oxide reaction body is 0.5μm, and the crystal water content of the aluminum oxide reaction body is 17wt%.
[0113] In S2, the heating rate was 1°C / min, the calcination temperature was controlled at 500°C, and the calcination time was 10 h, resulting in a particle size of 0.5 μm and a pore volume of 0.09 cm 3 / g, porous alumina with a pore size of 3nm.
[0114] In S3, the second hydrothermal reaction is carried out at 90° C. for 48 h.
[0115] Example 12
[0116] The difference between this embodiment and embodiment 1 is that in S1, triquaternary ammonium is replaced by trimethylammonium, the amount of trimethylammonium added is 1wt% of the aluminum salt, and the first hydrothermal reaction is carried out at 240°C for 4h. The chemical formula of the aluminum oxide reaction body obtained in this step is Al2O3·nH2O, wherein the value of n is 1.1. The particle size of the aluminum oxide reaction body is 1μm, and the crystal water content of the aluminum oxide reaction body is 17wt%.
[0117] In S2, the heating rate was 10 °C / min, the calcination temperature was controlled at 1200 °C, and the calcination time was 0.5 h, resulting in a particle size of 1 μm and a pore volume of 0.02 cm 3 / g, porous alumina with a pore size of 49nm.
[0118] In S3, the second hydrothermal reaction is carried out at 190° C. for 4 h.
[0119] Comparative Example 1
[0120] The difference between this comparative example and Example 1 is that this comparative example does not use homemade porous alumina, but uses homemade ordinary alumina (SAO-035EL, preparation conditions: aluminum salt is calcined at 1200°C), which has no porous structure and a particle size of 0.7 μm. Figure 2 shown.
[0121] The remaining preparation methods and parameters were the same as those in Example 1, and a modified alumina with a modification amount of 0.1% was obtained. The modification aid was attached to the surface of the alumina particles.
[0122] Comparative Example 2
[0123] The difference between this comparative example and Example 1 is that no modifying aid is added in S3.
[0124] Comparative Example 3
[0125] The difference between this comparative example and Example 1 is that in S3, the amount of piperidine used is 8 kg, that is, this comparative example is a modified porous alumina with a loading amount of the modification aid of 0.8 wt %.
[0126] Comparative Example 4
[0127] The difference between this comparative example and Example 1 is that in S3, the amount of piperidine used is 45 kg, that is, this comparative example is a modified porous alumina with a loading amount of the modification aid of 45 wt %.
[0128] Comparative Example 5
[0129] The difference between this comparative example and Example 1 is that commercially available porous alumina is directly used for step S3. The particle size of the porous alumina is 0.09 μm and the pore volume is 0.09 cm 3 / g, pore diameter is 4nm. The loading amount of the modification aid in the modified porous alumina is 0.8wt%.
[0130] Comparative Example 6
[0131] The difference between this comparative example and Example 1 is that commercially available porous alumina is directly used for step S3. The porous alumina has a particle size of 0.7 μm and a pore volume of 0.12 cm 3 / g, pore diameter is 4nm. The loading amount of the modification aid in the modified porous alumina is 0.2wt%.
[0132] Comparative Example 7
[0133] The difference between this comparative example and Example 1 is that commercially available porous alumina is directly used for step S3. The particle size of the porous alumina is 0.7 μm and the pore volume is 0.01 cm 3 / g, pore diameter is 2nm. The loading amount of the modification aid in the modified porous alumina is 0.2wt%.
[0134] Comparative Example 8
[0135] The difference between this comparative example and Example 1 is that commercially available porous alumina is directly used for step S3. The particle size of the porous alumina is 0.09 μm and the pore volume is 0.12 cm 3 / g, pore size is 2nm. The loading amount of the modification aid in the modified porous alumina is 0wt% (the pore size and particles are too small to achieve loading or coating, and a small amount of loading is more likely to volatilize during the drying process).
[0136] Comparative Example 9
[0137] The difference between this comparative example and Example 1 is that in S1, the amount of the doping aid added is 2 wt % of the aluminum salt, and the amount of the modified aid attached to the modified alumina is 0.1 wt %.
[0138] Comparative Example 10
[0139] The difference between this comparative example and Example 1 is that in S1, the doping aid is another pore-forming agent (ammonium bicarbonate). The amount of the modified aid attached to the modified alumina is 0.1 wt%.
[0140] Test example
[0141] Multiple characteristics of the modified alumina prepared in Examples 1 to 12 and Comparative Examples 1 to 10 are compared, and the results are shown in Table 1.
[0142] Among them, the particle size of porous alumina is tested by Malvern 3000 particle size test instrument, the pore volume and pore size data of porous alumina are tested by Micro equipment, the doping amount of modified additives is tested by ignition reduction test, the contact angle is tested by contact angle meter, and the HF acid removal amount is determined by testing the pH change of the electrolyte.
[0143] Table 1 Test results
[0144]
[0145]
[0146] From Table 1, we can get:
[0147] It can be seen from the results of Examples 1 to 12 that the preparation method provided in the embodiments of the present invention, by combining aluminum hydroxide and a doping aid, obtains a porous alumina having a porous structure, and then modifies the porous alumina. When it is used for coating a lithium-ion battery diaphragm, a diaphragm with high wettability and HF acid removal function can be obtained.
[0148] From the results of Examples 1 to 12 and Comparative Example 1, it can be seen that in the present invention, porous alumina can load more modification aids than conventional alumina, and conventional alumina cannot function if the loading amount is too small.
[0149] From the results of Examples 1 to 12 and Comparative Examples 2 to 3, it can be seen that in the present invention, when no modification aid is loaded or the modification aid loading amount is less than 1%, the wettability cannot be improved and hydrofluoric acid cannot be removed.
[0150] From the results of Examples 1 to 12 and Comparative Example 4, it can be seen that in the present invention, the loading amount of the modification aid is higher than 40%, HF adsorption cannot reach saturation, and the pore volume / pore diameter is reduced, which affects lithium ion transmission and increases costs.
[0151] From the results of Examples 1 to 12 and Comparative Examples 5 to 8, it can be seen that in the present invention, even if porous alumina with a porous structure is used together with a modification aid to prepare modified porous alumina, if any of the particle size, pore volume and pore size of the porous alumina is improperly set, the final modified porous alumina will not be able to effectively improve wettability and remove hydrofluoric acid.
[0152] From the results of Examples 1 to 12 and Comparative Example 9, it can be seen that in the present invention, if the amount of doping auxiliary agent is inappropriate, the morphology of the first alumina reactant will deteriorate, and alumina with a porous structure cannot be obtained after calcination, which will result in the final modified alumina being unable to effectively improve wettability and remove hydrofluoric acid.
[0153] From the results of Examples 1 to 12 and Comparative Example 10, it can be seen that in the present invention, if a conventional pore-forming agent is used instead of the doping aid in the present invention, alumina with a porous structure cannot be obtained after calcination, which results in the final modified alumina being unable to effectively improve wettability and remove hydrofluoric acid.
[0154] In summary, the modified porous alumina provided by the present invention can realize the setting of a thinner coating on the diaphragm, which is beneficial to improving the liquid retention and ion conductivity of the diaphragm. It can not only improve the wetting performance, but also effectively capture HF free in the electrolyte, thereby improving the reliability and safety of lithium-ion batteries.
[0155] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A modified porous alumina, characterized in that: The modified porous alumina comprises porous alumina and a modification aid loaded in the pore structure of the porous alumina; The modification aid includes at least one of pyridine, imidazole, indole, quinoline and morpholine; the mass ratio of the porous alumina to the modification aid is 100:1 to 100:40; The particle size of the porous alumina is 0.1 μm to 2 μm; The pore volume of the porous alumina is 0.01 cm 3 / g~0.1cm 3 / g; The pore size of the porous alumina is 3nm to 50nm.
2. A method for preparing the modified porous alumina powder according to claim 1, characterized in that: The following steps are involved: The aluminum salt, the doping aid and water are mixed and subjected to a first hydrothermal reaction to obtain an aluminum oxide reactant; The alumina reactant is dried and then calcined to obtain porous alumina; The porous alumina is mixed with a modification aid and water, subjected to a second hydrothermal reaction, and dried to obtain modified porous alumina.
3. The preparation method according to claim 2, characterized in that: The aluminum salt includes at least one of aluminum nitrate nonahydrate, aluminum nitrate, aluminum alcoholate and aluminum hydroxide; Preferably, the aluminum salt is selected from aluminum hydroxide.
4. The preparation method according to claim 2, characterized in that: The amount of the doping aid added is 0.01wt% to 1wt% of the aluminum salt; And / or, the doping aid includes at least one of triquaternary ammonium and trimethylammonium.
5. The preparation method according to claim 2, characterized in that: The temperature of the first hydrothermal reaction is 120° C. to 240° C., and / or the time of the first hydrothermal reaction is 4 h to 48 h.
6. The preparation method according to claim 2, characterized in that: The chemical formula of the aluminum oxide reactant is Al2O3·nH2O, wherein 1≤n≤2; and / or, the particle size of the alumina reactant is 0.1 μm to 2 μm; And / or, the alumina reaction body has a crystal water content of 17 wt% to 30 wt%.
7. The preparation method according to claim 2, characterized in that: The calcination temperature is 500°C to 1200°C; And / or, the calcination time is 0.5h to 10h; And / or, the heating rate during the calcination process is 1°C / min to 10°C / min.
8. The preparation method according to claim 2, characterized in that: The temperature of the second hydrothermal reaction is 90° C. to 190° C., and / or the time of the second hydrothermal reaction is 4 h to 48 h.
9. A battery separator, characterized in that: The battery separator comprises a separator substrate and a coating located on at least one side of the separator substrate, wherein the coating contains the modified porous alumina according to claim 1; Preferably, the contact angle between the battery separator and water is less than 35°.
10. A battery, characterized in that: The battery comprises the battery separator of claim 9.
Citation Information
Cited By
Nano porous alumina, preparation method and application thereof, and lithium ion battery diaphragm
CN121361814A